2011
DOI: 10.1016/j.socscimed.2011.09.033
|View full text |Cite
|
Sign up to set email alerts
|

Choreographies of sperm donations: Dilemmas of intimacy in lesbian couple donor conception

Abstract: Assisted conception involving donor insemination challenges cultural idioms of parenthood and family; there is now a growing body of work exploring how women and couples negotiate becoming a family in this way. But sperm donation also raises questions on the more intimate levels of sex, sexuality and sexual bodies, and these have received little sustained attention in the literature. Lesbian couples in the U.K. increasingly negotiate access to medicalised donor insemination, but many also conceive in informal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 12 publications
0
22
0
1
Order By: Relevance
“…These factors were also voiced by the participants in our study as reasons for choosing SI. One of the challenges of SI that was identified both in our study and by Nordqvist (2011) is the need to access and use sperm in a timely fashion, that is, while it is still mobile. Participants in our study were acutely aware of the urgency required to increase the likelihood of successful conception, and as such shared that they hurried to inseminate as soon as possible after the sperm was obtained.…”
Section: Discussionmentioning
confidence: 92%
“…These factors were also voiced by the participants in our study as reasons for choosing SI. One of the challenges of SI that was identified both in our study and by Nordqvist (2011) is the need to access and use sperm in a timely fashion, that is, while it is still mobile. Participants in our study were acutely aware of the urgency required to increase the likelihood of successful conception, and as such shared that they hurried to inseminate as soon as possible after the sperm was obtained.…”
Section: Discussionmentioning
confidence: 92%
“…Here, the donor is seen as a body part and objectified by means of the medical procedures applied. As noted by Nordqvist (2011b), couples have to reach a compromise between the need for the donor's semen and the reluctance to access it. Moreover, even though the psychological reduction of the donor to a 'vial of sperm' (Alessandra, non-biological mother, anonymous donation) or 'plasticine' (Sabrina, biological mother, anonymous donation) initially works to eliminate the 'threat of the interloper' (Ehrensaft, 2008) from the intimacy of baby-making, the donor's relevance in the family construction remains.…”
Section: Discussionmentioning
confidence: 99%
“…(Nordqvist, 2011b). On the one hand, their push-pull feelings towards the donor and their transfer of positive characteristics of the reproductive process between the clinic and the doctor medicalise and obscure any relationship they have with the donor.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we observed attitudes characteristic to the Turkish society in general; the presence of a medical condition for oocyte donation, female gender, being included in the 40 year age group, and high levels of income and high education were significant determinants. Yet, in many countries in the world, without medical necessity (among homosexuals as well as heterosexuals), having children through gamete donation optionally is legal, supported, and acceptable by a certain segment of society in England and Wales (17). The most important reason is considered that it can stem from social, cultural, religious, socio-economic, and educational differences between countries in the laws and opinions (7).…”
Section: Discussionmentioning
confidence: 99%